Endoscopic retrieval device for proximally migrated pancreatic and biliary stent: Wire‐guided spiral basket catheter. Issue 7 (29th August 2020) - Sano, Takanori; Miura, Shin; Masamune, Atsushi
Abstract : Watch a video of this article